The impact of digital Yao Jewelry on cultural inheritance/ Yan Li and Emilia Abdull Manan - Li, Yan; Abdull Manan, Emilia (Universiti Teknologi MARA, Perak, 2024)
Incorporating digital technology into cultural preservation endeavors has gained growing importance in recent years. This abstract is a study that examines the influence of digitalization on the cultural transmission of Yao jewelry, a traditional skill deeply rooted in the historical and cultural heritage of the Yao population. The Yao people, renowned for their exceptional silversmithing mastery, have a profound heritage of crafting jewelry that encapsulates their cultural essence and principles. The study examines using digital resources, such as 3D modeling and virtual reality, to document, showcase, and promote Yao jewelry. The main objective is to investigate the capabilities of modern technologies in improving the visibility and recognition of this art form, specifically among younger generations and a worldwide audience. While digitalization offers advantages like improved accessibility and broader audience reach, there are apprehensions about the authenticity and conservation of the traditional craftsmanship employed in the production of Yao jewelry. The study investigates the equilibrium between utilizing digital technology and preserving the authenticity of the craft. This study employed quantitative analysis to examine the utilization of digital technology in the conservation and advancement of Yao jewelry among various regions of the Yao community. The research seeks to discern patterns and themes about using digital tools to preserve culture, specifically in lesser-known rural regions where traditional traditions may be in danger of extinction. The study's primary objective is to enhance the ongoing discussion over the impact of digital technology on the conservation and advancement of traditional cultural practices.